Effects of ECAR process on the mechanical properties of explosively welded Al/ Cu/Al - Ghaffari, Sina (Taylor Francis, 2022)
Equal channel angular rolling (ECAR) is a severe plastic deformation method that coated plastic deformation of sheets. This research aims to analyse the effects of equal channel angular rolling feeding routes and the number of passes on the mechanical properties of explosive-welded Al/Cu/Al multilayer sheets. Based on this study, three layers of metal sheets (Al/Cu/Al) were prepared through the explosive welding process to achieve the goals. This multilayer material been passed through the ECAR process, to investigate the number of passes affections and two different feeding routes (A and C) on the mechanical properties of the explosive welded samples. To examine changes in hardness and strength of ECAR samples, micro-hardness tests and uniaxial tensile tests were adopted. The results demonstrate that tensile strengths and microhardness increase for both routes by the ECAR process; however, it decreases the ductility. The yield strength of three layers of sheets has been increased from 92 MPa to 118 MPa and 126 MPa at the routes A and C, respectively. The results show that the toughness of the route A is greater than route C.